2009
DOI: 10.1155/2009/849784
|View full text |Cite
|
Sign up to set email alerts
|

A Homogeneous HLA-B*27 Genotyping Assay Using Dried Reagent Mixtures

Abstract: Abstract. The presence of HLA-B*27 allele with patients suspected with ankylosing spondylitis can be used in the diagnostic process. We have developed an assay for typing for the HLA-B*27 in whole blood dried on sample collection cards using pre-dried reagent wells and homogeneous time-resolved fluorescence based PCR approach. Essentially only the sample needs to be added to the dry ready-to-use reaction well in order to start the homogenous amplification assay. The method was validated with 229 samples also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…87 Kiviniemi et al have reported using a combination of vacuum-and air-drying to stabilize PCR reagents. 88 Paraffinpassivation is another method of stabilizing reagents on-board microfluidic chips, in which reagents are added during assembly and then encapsulated in paraffin wax. 89 Glassification 90 is another method of reagent stabilization used in commercial products which includes the addition of a glass-forming filler material, such as glucose, sucrose, maltose or maltotriose, to produce material that is stable at room temperature using freeze-drying 91,92 or vacuum-drying.…”
Section: 81mentioning
confidence: 99%
“…87 Kiviniemi et al have reported using a combination of vacuum-and air-drying to stabilize PCR reagents. 88 Paraffinpassivation is another method of stabilizing reagents on-board microfluidic chips, in which reagents are added during assembly and then encapsulated in paraffin wax. 89 Glassification 90 is another method of reagent stabilization used in commercial products which includes the addition of a glass-forming filler material, such as glucose, sucrose, maltose or maltotriose, to produce material that is stable at room temperature using freeze-drying 91,92 or vacuum-drying.…”
Section: 81mentioning
confidence: 99%